Risk Factors of Local Wisdom in Pariaman City - Marni, Linda; Barlian, Eri; Fatimah, Siti; Muchtar, Bustari (Sumatra Journal of Disaster, Geography and Geography Education, 2020)
The purpose of this study is to explain the risk factors of local wisdom of the community in Pariaman City. This type of research is qualitative research, which is a study that tries to understand the phenomenon of the problem of risk factors for the spread of tuberculosis disease which is reviewed from local wisdom in the people of Pariaman City. Disasters include not only floods, landslides, land fires, earthquakes, and tsunamis, but disease outbreaks are also included in the disaster category. Therefore this event also requires mitigation and careful treatment scenarios related to disease outbreaks that may appear in the future and can be handled properly. The belief of the people in Pariaman city area of West Sumatra, pulmonary TB disease as a disease because tamakan, due to the use of others dislike, proven by the habit, the behavior of the community disposes of saliva carelessly on the ground, on the floor of the land house. Stigma is fear, shame as a TB sufferer, so there is still a lot of perception that people who call it long cough disease, cough 40 days, can also call it dry cough, and asthma. It is necessary to increase knowledge about pulmonary TB disease directly in the community can also by optimizing the role of community leaders, indigenous figures, local religious leaders as social support in prevention efforts in addition to being a